Respuesta :

Answer:      

A. x = 9

D. x = 0

Step-by-step explanation:

The formula to solve a quadratic equation of the form

[tex]ax^{2} +bx+c=0[/tex]

is equal to

[tex]x=\frac{-b(+/-)\sqrt{b^{2}-4ac}} {2a}[/tex]

in this problem we have            

[tex]6x^{2} -54x=0[/tex]              

so

[tex]a=6\\b=-54\\c=0[/tex]

substitute in the formula

[tex]x=\frac{-(-54)(+/-)\sqrt{-54^{2}-4(6)(0)}} {2(6)}[/tex]

[tex]x=\frac{54(+/-)54} {12}[/tex]

[tex]x=\frac{54(+)54} {12}=9[/tex]              

[tex]x=\frac{54(-)54} {12}=0[/tex]          

therefore

The solutions are x=0 and x=9